Pardal, Mafalda. (2023). The Cannabis Social Club, New York: Routledge - Rodríguez Mera, Andrés (2023)
The so-called Cannabis Social Club structure presents legal, semi-legal and illegal versions in various continents of the world. From a regulatory point of view, it is both a threat and an opportunity for the current International Drug Control Regime. This compilation work by Mafalda Pardal is an interdisciplinary analysis, with global pretensions, on this disruptive proposal -and collective action- of cannabis supply. Its findings and interpretations contribute to research, academic and institutional fields around drug policies, social movements, criminal policies, trade reforms and disputes over drug users' rights.